Value-Added Processing of Chicken Slaughterhouse Solid Waste: Pengolahan Berbasis Nilai Tambah Limbah Padat Rumah Potong Ayam - Suseto, Amaliya Tuzzur Rikhah Putri; Nurbaya, Syarifa Ramadhani; Oktarina, Pramitha Wahyu (Universitas Muhammadiyah Sidoarjo, 2025)
The chicken slaughterhouse business is one of the industries developed to fulfil the community's need for animal protein. Along with the increasing consumption of chicken meat by the community, the amount of waste generated by the Chicken Slaughterhouse (RPA) is also increasing. Waste generated in RPA is divided into two types, namely solid waste and liquid waste. Solid waste includes chicken feathers, rumen contents, and chicken manure, while liquid waste comes from blood, water used for washing chickens, and water used for cleaning equipment mixed with fat and blood. Based on observations, solid waste generated by PT Ciomas Adisatwa will be reprocessed into fertiliser or processed into flour that can be used as animal feed. Unutilised chicken waste can result in environmental pollution. The results showed that the production process carried out by PT Ciomas Adisatwa was in accordance with halal provisions and standards.